Analysis of Epigenetic Changes in Vitamin D Pathway Genes in Rheumatoid Arthritis Patients - Puncevičienė, Eglė; Gaiževska , Justina; Sabaliauskaitė, Rasa; Šnipaitienė, Kristina; Vencevičienė, Lina; Vitkus, Dalius; Jarmalaitė, Sonata; Butrimienė, Irena (Acta medica Lituanica, 2022)
Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease with complex etiopathogenesis launched by multiple risk factors, including epigenetic alterations. RA is possibly linked to vitamin D that is epigenetically active and may alter DNA methylation of certain genes. Therefore, the study aimed to evaluate the relationship between DNA methylation status of vitamin D signaling pathway genes (VDR, CYP24A1, CYP2R1), vitamin D level and associations with RA. Materials and Methods: Totally 76 participants (35 RA patients and 41 healthy controls) were enrolled from a case-control vitamin D and VDR gene polymorphisms study regarding age and vitamin D concentration. CpG islands in promoter regions of the VDR, CYP24A1, CYP2R1 genes were chosen for DNA methylation analysis by means of pyrosequencing. Chemiluminescent microplate immunoassay was used to assess 25(OH)D serum levels. RA clinical data, i.e. the disease activity score C-reactive protein 28 (DAS28 – CRP) as well as patient-reported outcome questionnaires were recorded. Results: The study showed similar methylation pattern in the promoter regions of vitamin D pathway genes in RA and control group with p>0.05 (VDR gene 2.39% vs. 2.48%, CYP24A1 gene 16.02% vs. 15.17% and CYP2R1 2.53% vs. 2.41%). CYP24A1 methylation intensity was significantly higher in compare to methylation intensity of VDR and CYP2R1 genes in both groups (p<0.0001). A tendency of higher vitamin D concentration in cases having methylated VDR (57.57±28.93 vs. 47.40±29.88 nmol/l), CYP24A1 (53.23±26.22 vs. 48.23±34.41 nmol/l) and CYP2R1 (60.41±30.73 vs. 44.54±27.63 nmol/l) genes and a positive correlation between VDR, CYP2R1 methylation intensity and vitamin D level in RA affected participants was revealed (p>0.05). A significantly higher CYP24A1 methylation intensity (p=0.0104) was detected in blood cells of vitamin D deficient (<50 nmol/l) RA patients vs. vitamin D deficient controls. Conclusions: Our data suggests some indirect associations between DNA methylation status of vitamin D pathway genes and vitamin D level in RA.